Separation of palm mesocarp fiber and nut by air classifier using air disturbance system - Zakaria, Ahmad Hafizuddin; Mohd Salleh, Mohamad Amran; Ismail, Mohd Halim Shah; Abdul Aziz, Mustafa Kamal (2018)
The air classifier is a system that used the rising air to separate the specific particles from other mixtures by applying the principle of gravity and air velocity. Air classification is a popular method used by the Malaysian palm oil mill industry to separate the mixture of palm mesocarp fibres and nuts kernel shell (press cake). However, current technology that used by the local palm oil mill industry usually based on know-how without supporting scientific data to improve the separation efficiency. The mesocarp fibres properties typically tend to stick to each other’s after the screw press process affected the ability of separation. The result shows the solution of the previous study where the clod formation of fibre became the main obstacle by introducing the air disturbance system. This system introduces air turbulence to the separator column to break the clod formation of fiber and improve the separation efficiency by 30%. This study will create a foundation to enhance the understanding of the fundamental of air classification and enhance its design efficiency.